A Sustainable Approach: Repurposing Red Beetroot Peels for Innovative Meringue Products - Oana Emilia Constantin; Florina Stoica; Silvia Lazăr (Mistrianu); Doina Georgeta Andronoiu; Mihaela Turturică; Nicoleta Stănciuc; Roxana Nicoleta Rațu; Constantin Croitoru; Gabriela Râpeanu (Foods)
With the increasing global demand for sustainable and eco-friendly food items, it is imperative to investigate alternate sources of natural pigments. The red beetroot (Beta vulgaris L.) is a traditional food in many countries and a rich bioactive compound known for its beneficial properties. Beetroot peel, a by-product of beetroot food processing, is often discarded, contributing to environmental damage. This research explores the potential of beetroot peel (BP) powder as a natural pigment in food products and its functional benefits. The study focuses on incorporating BP powder into meringues, aiming to create a value-added product with enhanced properties, particularly antioxidant activity. Various amounts of BP powder (4–10%) were added to meringue formulations, and the effects on the resulting meringues’ physicochemical properties, sensory qualities, and phytochemical profiles were assessed during 21 days of storage. The research revealed that BP powder, besides its function as a natural colorant and the pleasing pink hue it imparts to meringues, also enhances antioxidant activity due to its high phenolic concentration. BP powder was also incorporated to enhance the meringues’ overall sensory characteristics, improving their flavor and texture. The research findings indicate that BP has the potential to be used as a natural food ingredient to promote human health, resource-use efficiency, and a circular economy.